Provisioning food given by visitors to alpha-male long-tailed macaques at recreation forest, all of them are halal - Rosyid Ridlo Al Hakim; Erie Kolya Nasution; Rizaldi Rizaldi; Siti Rukayah (Journal of halal product and research (JPHR), 2021)
The long-tailed macaque (Macaca fascicularis Raffles, 1821) is a non-human primate (NHP) species with social status in its group. Macaca fascicularis living in groups and social castes. Alpha males lead their group. Alpha males will have greater access to food than individuals with lower social castes. The content of feed eaten by animals, of course, will affect health. Various biological processes occur, from the food eaten by animals to affect the health of human life. If the food eaten is toxic, it will be hazardous to the animal's metabolism for life. According to a Muslim perspective, how much better food can be eaten is included in Halal products. Including, in this case, food ingredients for feed, if it comes from ingredients that are included in the halal category, this will provide animal welfare. This study seeks to explain how visitors' feed types (provisioning food) to alpha-male Macaca fascicularis at Mbah Agung Karangbanar Recreation Forest, Banyumas, Central Java, Indonesia. This study used behavioral coding to measure the frequency and quantity of eating behavior for ten days based on visitor feeding. The remainder of the provisioning food found is recorded as data on the type of provisioning food. Based on the study results, the alpha-male was noted to eat provisioning food such as peanuts, bananas, sweet potatoes, snacks, and foods mixed with soy sauce given by visitors. All of them are halal because they eat visitors every time they come to a tourist location. Alpha-male was noted to have no interest in the carcasses found, so they did not eat them.